Revisiting responsible innovation in the knowledge production of Islamic banking and finance - Sunze Yu; Haotian Shi (Journal of Responsible Innovation)
This perspective paper speaks to the study by Hilmi (2018. ‘Responsible innovation in the financial sector: an Islamic perspective.’ Journal of Responsible Innovation 5 (2): 247–252. https://doi.org/10.1080/23299460.2018.1457400) published in the Journal of Responsible Innovation, Volume 5, 2018  – Issue 2. Hilmi’s study examines responsible innovation in the financial sector from an Islamic perspective. Although he integrates the concept of responsible innovation with Islamic banking and finance (IBF), many have questioned whether IBF, in its current form, is authentically Islamic – or at the very least, this claim is widely contested. In other words, whether IBF truly embodies responsible innovation remains subject to significant scrutiny. Adopting a Schumpeterian lens, this perspective paper argues that IBF is on the cusp of its second creative destruction through responsible innovation. By outlining three delimitations, this perspective paper contributes to broader discussions on responsible innovation in the knowledge production of IBF.